‘Urf: Medinan’s Tradition as a Shari'a Business Law - Lukman Nugraha, Ahmad; Abdul Aziz, Muhammad; Huda, Miftahul (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2023)
This paper aims to define 'urf and its foundations in the Qur'an and Hadith as well as the implementation of the 'urf method in islamic business. The research method used in this paper is qualitative with a normative juridical approach. The findings in this paper are that the Qur'an and hadith underlie the use of 'urf as a islamic business solution which certainly does not conflict with existing texts. 'Urf is often applied in sharia business through aspects of business transactions, profit taking from sellers of goods and services, and determination of wages. 'Urf can be applied in sharia business with several conditions, namely: 1) The business tradition does not conflict with the texts, (2) the business tradition is long-term, (3) the business tradition is known to the general public, (4) the business tradition is innovative according to space and time